2010
DOI: 10.1258/ebm.2009.009285
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis caused by an inhibitor of NO production in the decidua of rat from mid-gestation

Abstract: We previously reported that nitric oxide (NO) is first detected in the uterus of a pregnant rat on gestational day 13.5 (GD13.5) and that NO levels peak on GD17.5. In addition, NO production in the uterus is mainly derived from the decidua and not the myometrium. The aim of the present study was to reveal the role of NO that peaked on GD17.5 of gestation in the decidua. To inhibit NO production, pregnant rats were continuously administered by an nitric oxide synthase inhibitor, N(G)-nitro-L-arginine-methyl est… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…For instance it may be one of the factors required for platelet survival and the elevation of endogenous NO can play an important role in these mechanisms, as NO can be considered a central effector in the regulation of both cell survival and apoptosis [Choi et al, 2002]. A key role of NO bioavailability in fatal arterial hypertension [Hu et al, 2010], in gestation [Suzuki et al, 2010], in liver fibrosis resolution [Mòdol et al, 2011], and in the regulation of erythrocytes survival was recently demonstrated [Nicolay et al, 2008; Chowdhury et al, 2010]. Varying kinases (PKA, AKT, calmodulin‐dependent kinase II or AMP‐activated protein kinase), dependent on the stimuli applied, appear to be involved in eNOS phosphorylation and activation.…”
Section: Discussionmentioning
confidence: 99%
“…For instance it may be one of the factors required for platelet survival and the elevation of endogenous NO can play an important role in these mechanisms, as NO can be considered a central effector in the regulation of both cell survival and apoptosis [Choi et al, 2002]. A key role of NO bioavailability in fatal arterial hypertension [Hu et al, 2010], in gestation [Suzuki et al, 2010], in liver fibrosis resolution [Mòdol et al, 2011], and in the regulation of erythrocytes survival was recently demonstrated [Nicolay et al, 2008; Chowdhury et al, 2010]. Varying kinases (PKA, AKT, calmodulin‐dependent kinase II or AMP‐activated protein kinase), dependent on the stimuli applied, appear to be involved in eNOS phosphorylation and activation.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with these findings, increased vasoconstriction of human stem villous feto-placental arteries [47] and increased ovine umbilical vascular resistance [48] are caused by an NOS inhibitor, N G -monomethyl- l -arginine. Suzuki et al showed that N G -nitro- l -argininemethyl ester, an NOS inhibitor, caused apoptosis in the decidua, suggesting that NO in the decidua is essential to cell survival and the maintenance of uterine formation [49]. …”
Section: Roles Of No and Adma In Compromised Pregnanciesmentioning
confidence: 99%
“…In the literature, ambient air pollutants have been associated with adverse obstetric outcome such as low birth weight, 21,22 intrauterine growth restriction, [23][24][25] preterm delivery, [25][26][27] and certain congenital anomalies such as the increase in mainly cardiovascular anomalies with exposure to elevated carbon monoxide (CO), O 3 , particulate matter <10 mmol/L (PM 10 ), and SO 2 levels. [28][29][30][31] For nonsyndromal oral-facial clefts, this relationship remains unclear, as it was reported to increase with increasing proximity to the municipal solid waste incinerator, 32 to have no relationship with traffic exposure 32 as well as being linked to outdoor O 3 . 33 Taken together, the most likely reason for the conflicting literature and the largely futile attempts in elucidating the underlying aetiological mechanisms for the formation of isolated oral-facial clefts is the permutation of and possibly sequential interactions in these factors that result in the ultimate occurrence of oral-facial clefts as well as the likelihood that isolated CL and isolated CP have different aetiologies.…”
Section: Discussionmentioning
confidence: 99%
“…37 Moreover, in an animal study, NO was found to peak in the decidua and thought to be essential for the maintenance of the cell survival. 30 The NO is also involved in the adjustment of the proper timing of blastocyst implantation and supporting fetal growth. 38 As well, it is protective against infection, but by the same token it can damage tissues, proteins, and DNA.…”
Section: Discussionmentioning
confidence: 99%